Correlation Between Gender and Knowledge, with Practice and Referral Rate of Continuum Rehabilitation Cases by General Practitioners - Hari Hari Peni Julianti; Angela BM Tulaar BM Tulaar; Tirza Z Tamin; Tanti Ajoe Kesoema,; Endang Ambarwati,; Sri Wahyudati (Indonesian Journal of Physical Medicine & Rehabilitation, 2019)
Introduction: Indonesian Health Ministry had a strategy to make the primary care, including rhabilitation program by continuum of care. The purpose of this study was to determine factors related to the levelof knowledge, practice, and referral for continuum care cases that required rehabilitation services in Primary Health Care Doctors.Methods: The study design was cross-sectional. Participants were 23 Primary Health Care Doctors in Wonosobo District. Data collection was conducted in December 2017. The independent variablesconsist of gender, length of work, employment status, while the dependent variables were the level of knowledge, practice and referral cases of maternal, infants and toddlers, adolescents, adults and elderly.The measuring instrument was a questionnaire. Data were tested with chi-square, significance level <0.05.Results: Gender has correlation with the level of knowledge in maternal cases (PR = 0.121, 95% CI = 0.017-0.087, p = 0.026). Gender has correlation to the level of practice in maternal case (PR = 0.121,95% CI = 0.017-0.867, p = 0.026). Employment status has correlation to the referral rate of elderly cases(PR = 10.500, 95% CI = 1.015-108.577, p = 0.029).Conclusion: Gender has correlation with the level of knowledge and practice of maternal cases. Employment status has correlation with the level of referral rate of elderly cases.Keywords: Primary care doctors, Knowledge, Referral, Continuum Rehabilitation